The Development of A Bioassay Based on Heterologous Expression of M2 Ion-Channel Protein - Prasetyoputri, Anggia; Yuliaty, Neti; Tuharea, Warda; Febyanti, Alisin Febyanti; Sunarko, Bambang; Atmosukarto, Ines I.C (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
Emerging resistant viralÂ strains combined with theÂ limited availability of antiviralsÂ inÂ a pandemic scenario highlight the need for the development of novel influenza antivirals. A bioassay based on the M2 protein of influenza virusÂ -Â a potential target for antivirals - was developed to screen endophytic microbial extracts. M2 can be synthesized using PCR, thus eliminating the need for the handling of infectious specimen. Following cloning of the M2 gene into a pET backbone, the resultant plasmid was transformed into BL21 (DE3) pLyss E. coliÂ cells.Â Cultures of these cells were set up at 37ï°C following inoculation with a starter culture, to reach an ODÂ atÂ 600nmÂ (OD) ofÂ 0.4-0.6.Â OnceÂ atÂ theÂ requiredÂ OD,Â theÂ cultureÂ wasÂ splitÂ inÂ twoÂ aliquotsÂ and expressionÂ ofÂ theÂ M2Â proteinÂ wasÂ inducedÂ inÂ oneÂ ofÂ theÂ duplicatesÂ withÂ theÂ additionÂ ofÂ isopropylÂ Î²-Dthiogalactopyranoside (IPTG). Bacterial growth was monitored at 60 -minute intervals. Exogenous expression ofÂ theÂ M2Â proteinÂ hasÂ beenÂ reported toÂ decreaseÂ hostÂ cellsÂ viability,Â resultingÂ inÂ lowerÂ OD 600 values. Our resultsÂ suggestÂ thatÂ theÂ M2Â proteinÂ wasÂ expressedÂ andÂ thatÂ overexpressionÂ ofÂ thisÂ proteinÂ resultedÂ in consistently lower OD 600Â values of induced cultures compared with that of uninduced cultures. Based on this principle,Â extractsÂ canÂ beÂ screenedÂ forÂ theirÂ abilityÂ toÂ blockÂ M2Â functionÂ asÂ identifiedÂ byÂ increasedÂ OD 600 values. Â Keywords: influenza, M2, bioassay, gene synthesis, antiviral